2022
DOI: 10.3389/fbioe.2022.856591
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy: A Novel Technology for Gastric Cancer Diagnosis

Abstract: Gastric cancer is usually diagnosed at late stage and has a high mortality rate, whereas early detection of gastric cancer could bring a better prognosis. Conventional gastric cancer diagnostic methods suffer from long diagnostic times, severe trauma, and a high rate of misdiagnosis and rely heavily on doctors’ subjective experience. Raman spectroscopy is a label-free molecular vibrational spectroscopy technique that identifies the molecular fingerprint of various samples based on the inelastic scattering of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 79 publications
0
26
0
Order By: Relevance
“…Since the composition of nucleic acids, proteins and lipids in tumor cells are dramatically different from normal brain cells, while Raman spectroscopy is able to identify the chemical composition of a sample by measuring the Raman shift caused by the difference between the frequency of the scattered light and incident light in the Raman effect ( 33 ), as Ji reported that glioma and normal brain tissues have significantly different spectral peaks at 1080 cm-1 (nucleic acid), 2845 cm-1 (lipid) and 2930 cm-1 (protein) positions ( 34 ). Instead, the differences just depend on their chemical group, independent of the excitation wavelength, while the intensity of Raman peaks is related to the excitation light wavelength, power and concentration of the measured substance ( 35 ), so the Raman spectroscopy have the possibility to evaluate tumors and normal tissues according to the differences ( Figure 1 ) ( 12 ). Currently, the major diagnostic methods for glioma in clinical practice include imaging and pathology, and imaging primarily covers CT, MRI and PET.…”
Section: Application Of Raman Spectroscopy In Tumormentioning
confidence: 99%
“…Since the composition of nucleic acids, proteins and lipids in tumor cells are dramatically different from normal brain cells, while Raman spectroscopy is able to identify the chemical composition of a sample by measuring the Raman shift caused by the difference between the frequency of the scattered light and incident light in the Raman effect ( 33 ), as Ji reported that glioma and normal brain tissues have significantly different spectral peaks at 1080 cm-1 (nucleic acid), 2845 cm-1 (lipid) and 2930 cm-1 (protein) positions ( 34 ). Instead, the differences just depend on their chemical group, independent of the excitation wavelength, while the intensity of Raman peaks is related to the excitation light wavelength, power and concentration of the measured substance ( 35 ), so the Raman spectroscopy have the possibility to evaluate tumors and normal tissues according to the differences ( Figure 1 ) ( 12 ). Currently, the major diagnostic methods for glioma in clinical practice include imaging and pathology, and imaging primarily covers CT, MRI and PET.…”
Section: Application Of Raman Spectroscopy In Tumormentioning
confidence: 99%
“…Relevant studies have shown that analysing the fingerprint region alone is superior to analysing the HW region alone, but analysing the fingerprint and HW regions together is optimal [17] , [18] . In addition, in previous Raman spectroscopy studies, spectral baselines were removed in the spectral preprocessing stage using methods such as adaptive iteratively reweighted penalized least squares (airPLS) algorithm [19] , [20] , [21] . However, Tomasz et al speculated in the study that there is a correlation between the Raman baseline and the fluorescence background of the sample [22] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the small characteristic differences among Raman spectra, computer methods such as machine learning and deep learning are often used to differentiate the spectra when analysing them. Algorithms such as the principal component analysis-linear discriminant analysis (PCA-LDA), K-nearest neighbour (KNN), partial least squares-discriminant analysis (PLS-DA), support vector machine (SVM), artificial neural network (ANN), and convolutional neural network (CNN) algorithms are widely used [20] , [26] , [27] . PCA can perform linear dimensionality reduction by orthogonal transformation [28] and reduce the difficulty of data analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Raman spectroscopy is a nondestructive and effective tool that has been applied successfully to various fields such as: medicine [ 19 , 20 , 21 , 22 , 23 ], dental research [ 24 , 25 , 26 ], biology [ 27 ], food safety [ 28 ], chemistry [ 29 ], pharmacy [ 30 ], etc. Material identification and its structural characterization are complex, since Raman scattering acts at various levels, from surface to the depth of the samples.…”
Section: Introductionmentioning
confidence: 99%